KECENDERUNGAN MINAT USAHA ONLINE DI MASA PANDEMI COVID-19 PADA KARYAWAN SWASTA DI KAWASAN INDUSTRI CIKARANG - Indra Permana; Dian Rachmawati Afandi (Perwira Journal of Economics & Business, 2021)
The increasing number of unemployed in Indonesia due to the impact of the Covid-19 outbreak is increasing rapidly in 2020. In addition, losses in the economy, especially trading, have also been the cause of the economic crisis. In supporting the government's program to reduce the number of transmissions of the Covid-19 virus, online business is one way to make it easier for customers to make buying and selling transactions. This study aims to examine the influences of entrepreneurship, motivation and family environment on online business interest during the Covid-19 pandemic on private employees in the Cikarang industrial area.The sampling method used is Probability Sampling Design by providing equal opportunities for each element (member) to be selected as a member of the sample. The population in this study were private employees in the Cikarang industrial Area. The results of the study proves that there is a positive and significant influence between entrepreneurial knowledge, motivation and family environment on online business interest. The three variables also have a simultaneous influence on online business interest during the Covid-19 pandemic on private employees in the Cikarang industrial area.